Contrast‐enhanced harmonic endoscopic ultrasonography for differential diagnosis of submucosal tumors of the upper gastrointestinal tract. Issue 10 (26th September 2017) - Kamata, Ken; Takenaka, Mamoru; Kitano, Masayuki; Omoto, Shunsuke; Miyata, Takeshi; Minaga, Kosuke; Yamao, Kentaro; Imai, Hajime; Sakurai, Toshiharu; Watanabe, Tomohiro; Nishida, Naoshi; Chikugo, Takaaki; et al.
Abstract: Background and Aim: The study aims to evaluate contrast‐enhanced harmonic endoscopic ultrasonography (CH‐EUS) for the differential diagnosis of submucosal tumors (SMT) of the upper gastrointestinal tract. Methods: Between June 2008 and May 2015, 157 consecutive patients with submucosal lesions of the upper gastrointestinal tract were evaluated by CH‐EUS. This was a single‐center retrospective analysis of prospectively collected data in a registry. The data from 73 patients who later underwent surgical resection were analyzed in this study. Surgical specimens served as the final diagnoses. The two CH‐EUS variables of blood flow (hyper‐enhancement vs hypo‐enhancement) and homogeneity of enhancement pattern were evaluated. Results: The final diagnoses were 58 gastrointestinal stromal tumors (GISTs) and 15 benign SMTs (two lipomas, five leiomyomas, five schwannomas, two glomus tumors, and one ectopic pancreas). On CH‐EUS, 49 of 58 (84.5%) GISTs presented with hyper‐enhancement, whereas 4 of 15 (26.7%) benign SMTs showed hyper‐enhancement; 21 of 58 (36.2%) GISTs showed inhomogeneous contrast enhancement, while only 2 of 15 (13.3%) benign SMTs demonstrated inhomogeneous contrast enhancement. If hyper‐enhancement was considered to indicate GISTs, the sensitivity, specificity, and accuracy were 84.5%, 73.3%, and 82.2%, respectively. If inhomogeneous enhancement was considered to indicate GISTs, the sensitivity, specificity, and accuracy were 36.2%, 86.7%, and 46.6%, respectively. In lesions of less than 2 cm, hyper‐enhancement was a more sensitive indicator of GISTs than inhomogeneous enhancement. Conclusions: Hyper‐enhancement and inhomogeneous enhancement were found to be a characteristic of GISTs. CH‐EUS was useful for discrimination of benign SMTs from GISTs.